A study on optimization method of a powertrain mounting system with a three-cylinder engine. (June 2017) - Liu, Xiao-Ang; Shangguan, Wen-Bin; Lv, Zhao-Ping; Ahmed, Waizuddin; Zhu, Weidong
Compared with unbalance forces and moments of four- and six-cylinder engines, forces and moments applied to the engine block from a three-cylinder engine are large and the mechanism for balancing the unbalance forces are complex. So design of a mounting system for the powertrain with a three-cylinder engine is more challenging. This paper presents the analytical methods for obtaining the unbalance forces and moments applied to the engine block for a three-cylinder engine with or without balance measures, and develops a design methodology for the Powertrain Mounting System with a three-cylinder engine. The unbalance forces and moments generated by cylinders, crank and connecting rod mechanisms and applied to the engine block are analyzed firstly. Then, three balance methods for reducing the forces and moments applied to the engine block are proposed and discussed. Three balance measures are described and analyzed. The methods for estimating forces and moments applied to the engine block under the three balance measures are developed and compared. Thirdly, an optimization method is proposed to estimate mount stiffness based on minimization of mount forces transmitted to the car body or sub-frame, along with meeting requirements for placing natural frequencies of the powertrain in prescribed ranges and those for maximizing modal energy distributions of the powertrain in six directions. An example is given to validate the calculation methods and design philosophy for the mounting system of a powertrain with a three-cylinder engine.